Solar-terrestrial magnetic activity and space environment : proceedings of the COSPAR Colloquium on Solar-Terrestrial Magnetic Activity and Space Environment (STMASE), held in the NAOC in Beijing, China, September 10-12, 2001 /: proceedings of the COSPAR Colloquium on Solar-Terrestrial Magnetic Activity and Space Environment (STMASE), held in the NAOC in Beijing, China, September 10-12, 2001. (2002) - Unknown
No abstract available